1995
DOI: 10.7751/telopea19953017
|View full text |Cite
|
Sign up to set email alerts
|

Systematic studies in the eucalypts. 7. A revision of the bloodwoods, genus Corymbia (Myrtaceae)

Abstract: 185Hill, KD. & Johnson, L.A.S. (National Herbarium of New South Wales, Royal Botanic Gardens, Sydney, Australia 2000) 1995. Systematic studies in the eucalypts. 7. A revision of the bloodwoods, genus Corymbia (Myrtaceae). Telopea 6(2-3): 185-504. A taxonomic revision of the bloodwoods (including 'ghost gums') is presented. Previous cladistic studies in the eucalypts are re-evaluated; new phylogenetic analyses are presented for the Angophora + Eucalyptus sens. lat. group, the Angophora + blood wood dade, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
269
7
8

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(298 citation statements)
references
References 19 publications
(67 reference statements)
14
269
7
8
Order By: Relevance
“…By morphology and fossil record, Eucalyptus is the closest clade to Corymbia and Angophora. It is not clear whether this failure to amplify Corymbia specific SSRs in Eucalyptus, while successfully amplifying all the loci in Eucalyptopsis group, reflects relative evolutionary distances, since the branch lengths for the Eucalyptopsis group and Eucalyptus relative to Corymbia were inconsistent between datasets (e.g., Hill and Johnson, 1995;Steane et al, 2002;Wilson et al, 2001;Parra-O et al, 2006). This observation may indicate that Eucalyptus is a faster evolving clade, thereby accumulating more mutations in the flanking sequences of the SSRs.…”
Section: Ascertainment Biasmentioning
confidence: 78%
See 3 more Smart Citations
“…By morphology and fossil record, Eucalyptus is the closest clade to Corymbia and Angophora. It is not clear whether this failure to amplify Corymbia specific SSRs in Eucalyptus, while successfully amplifying all the loci in Eucalyptopsis group, reflects relative evolutionary distances, since the branch lengths for the Eucalyptopsis group and Eucalyptus relative to Corymbia were inconsistent between datasets (e.g., Hill and Johnson, 1995;Steane et al, 2002;Wilson et al, 2001;Parra-O et al, 2006). This observation may indicate that Eucalyptus is a faster evolving clade, thereby accumulating more mutations in the flanking sequences of the SSRs.…”
Section: Ascertainment Biasmentioning
confidence: 78%
“…This observation may indicate that Eucalyptus is a faster evolving clade, thereby accumulating more mutations in the flanking sequences of the SSRs. SSR analysis excluded Arillastrum because available morphological and molecular data (Hill and Johnson, 1995;Udovicic and Ladiges, 2000;Wilson et al, 2001;Steane et al, 2002) put this genus the farthest from Corymbia among the eucalypts; Ladiges et al (2003) suggested, based on biogeography, that the divergence of Arillastrum from the other eucalypt genera may be as old as Late Cretaceous (70 MYA; see also Crisp et al (2004). These data suggested a potentially low prospect of transferring Corymbia SSRs to Arillastrum.…”
Section: Ascertainment Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Corymbia, estabelecido a partir de 1995 como um novo grupo taxonômico de Myrtaceae (Hill & Johnson, 1995), é composto por aproximadamente 113 espécies arbóreas anteriormente incluídas em Eucalyptus L'Hér. No entanto, os estudos relativos às atividades biológicas desse grupo têm sido efetuados, especialmente, envolvendo a espécie Corymbia citriodora (Hook.)…”
Section: Introductionunclassified